Translation Strategies For Political Terms In Trafficking In Person (Tip) Situation Assessment Guidelines - Risky Dinahari, Diorani; Putu Krisnawati, Ni Luh; Rajeg, Gede Primahadi Wijaya (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study examines the translation strategies used for political terms in the Trafficking in Person (TIP) Situation Assessment Guidelines by the International Organization for Migration (IOM). The phenomenon under investigation is the complexity of translating legal and political terms, where accuracy is critical to ensure legal clarity and policy effectiveness. Translation errors may lead to misinterpretations that affect legal proceedings and policy implementation. The research is grounded in Vinay and Darbelnet’s (1995) translation theory, which categorizes strategies into direct and oblique translation, and Miriam Budiardjo’s (2008) concepts of political terms, including state, power, and policy. A qualitative case study approach is employed, analyzing the translation of political terms from English to Indonesian using document analysis and comparative methods. Data is drawn from both the English and Indonesian versions of the TIP Situation Assessment Guidelines, focusing on translation strategies such as borrowing, calque, literal translation, transposition, modulation, equivalence, and adaptation. The findings will contribute to understanding how translation strategies influence the accuracy and effectiveness of legal and political text translations, ensuring that crucial information regarding human trafficking policies is accurately conveyed across languages.